Anatomia do lenho do gênero Calycophyllum A. DC. (Rubiaceae) - Baldin, Talita (2015)
The Rubiaceae family is one of the main botanical families of Flowering Plants Dicotyledonous, being the fourth with the largest number of representatives and, even being cosmopolitan, their species are preferably the warmer regions. Since its original description, the family went through some taxonomic changes because of their significant morphological diversity. The study of species of the genus Calycophyllum A. DC. (C. spruceanum f. brasiliensis, C. candidissimum, C. multiflorum e C. spruceanum) aims to provide information about anatomical characters of taxonomic value, recognize the affinity of anatomical groups, comparing the species and investigate the relationship between anatomy and wood technology. The wood samples were gained from different scientific institutions, such as the Jodrell Laboratory (Kew Gardens, London), the Institute of Technological Research of the State of São Paulo (IPT) and the German University Black Forest Academy (BFA). The cutting blades and macerate were obtained by using the standard technique (BURGER; RICHTER, 1991) and the modified method of Franklin (KRAUS; ARDUIN, 1997), respectively. The wood descriptions were performed in the wood anatomy lab, Federal University of Santa Maria, and followed the recommendations of the IAWA Committee (1989). The cluster analysis included anatomical characters of the species described in this study and also those of other species of Rubiaceae described in the literature. Most anatomical characteristics agreed with the common pattern described in the Rubiaceae family, and allowed grouping them in the wood structure type II. These characteristics however, did not match with the anatomical pattern of the Ixoroideae subfamily. The cluster analysis recognized four main groups. The species of the genus Calycophyllum formed highly similar grouping with each other, which indicates a large structural homogeneity of their woods, more likely due to the high number of shared anatomical features. It is assumed that the anatomical characteristics of wood species investigated confer to the timber high specific gravity, resistance to mechanical stress, low shrinkage, permeability and good natural durability.